KOORDINASI KESBANGPOL DAN LINMAS DENGAN KPUD DALAM PILKADA DI KABUPATEN KARO - Arifin Sihombing; Salpinus Ginting (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) UDA, 2020)
The 2018 local election system has come to the attention of the Karo people. Society views candidate pairs based on ethnicity, race and religion not from career backgrounds and competencies, which raises issues that are not good and quite serious. Therefore the KESBANGPOL (United Nations and Politic) and LINMAS (Cross Society) and the KPUD (regional election commission) coordinate to provide socialization and guidance to the public so that they are smart in their choices so as to produce quality regional heads. This study aims at finding out how the Coordination of the KESBANGPOL and LINMAS Karo Regency together with the Regional Election Commission (KPUD) conducted a Regional Election in the District of Karo. This research is descriptive qualitative type. The results of observations and interviews by the author of the Karo district Election Commission and KESBANGPOL and Karo district LINMAS in connection with the 2018 Regional Head General Election, are that the two government agencies have coordinated the implementation of the Regional Head Election in Karo Regency starting from preparation, simulation title voting, carrying out political socialization, and increasing the participation of joint voters. Other coordination is facing vulnerability in elections, black campaigns and political money as well as coordination in efforts to create conducive situations and conditions in dealing with the 2018 elections. The impact makes the implementation of Regional Head Election in Karo district can run well, especially the regional head elections of 2018.